PPS / PPO composite material and preparation method thereof
By combining PPO resin, organic HGS, functional POSS, and improving compatibility and dispersion through epoxy reaction, the problem of poor mechanical properties of PPS materials is solved, and the excellent mechanical properties, low dielectric properties and low linear thermal expansion coefficient of PPS/PPO composite materials are achieved, which is suitable for the 5G/6G communication field.
Patent Information
- Application Number
- CN202411654228.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-19
- Publication Date
- 2025-02-25
AI Technical Summary
While maintaining excellent dielectric properties, existing PPS materials have poor mechanical properties and high prices, which are not suitable for large-scale production and strict usage requirements of 5G base stations.
By combining PPO resin, organic HGS, functionalized POSS, and reacting the epoxy groups of PPO-g-GMA, organic HGS, functionalized POSS, and organic zirconium phosphotungate with PPS and PPO end groups, the compatibility and dispersion of these materials in PPS/PPO composite materials are improved, thereby reducing the dielectric constant and linear thermal expansion coefficient.
It realizes excellent mechanical properties, low dielectric properties and low linear thermal expansion coefficient of PPS/PPO composite materials, and is suitable for high-frequency signal transmission in the field of 5G/6G communications.
Smart Images

Figure CN119505536A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of materials, and in particular to a PPS / PPO composite material and a preparation method thereof. Background Art
[0002] The rapid development of 5G communication technology is driving the miniaturization and high-frequency development of communication devices. This reduction in device size presents new challenges for the proper transmission of high-frequency signals. To ensure efficient transmission of high-frequency signals and minimize signal loss, device materials are required to have low dielectric constants and low dielectric loss. Practical communication applications require materials that further reduce dielectric constants and loss while also ensuring mechanical properties and other performance characteristics meet the stringent requirements of 5G base stations.
[0003] Polyphenylene sulfide (PPS) has a wide range of applications and its excellent dielectric properties can meet the needs of high-frequency communications. The dielectric constant of PPS at 1 GHz is 3.2 and the dielectric loss is 2.53×10 -3 However, compared with other special engineering plastics, its mechanical properties are slightly worse and its price is slightly more expensive, which is not conducive to large-scale production and application. In order to expand its scope of application, PPS materials need to be modified to improve their mechanical properties while maintaining their dielectric properties. First, in order to improve the dielectric properties of PPS, other engineering plastics can be added to PPS resin and mechanically blended at high temperature to obtain PPS alloy materials. By introducing other low-polarity or non-polar resins to reduce the polarity of the PPS composite material, its dielectric constant is reduced. Polyphenylene ether (PPO) in engineering plastics has no strong polar groups in its molecular structure, and its comprehensive properties including dielectric properties, dimensional stability, and mechanical properties are also good. Therefore, it is considered to use the above-mentioned engineering plastics as modified materials for low-dielectric PPS composite materials to further improve the dielectric properties of PPS.
[0004] Generally speaking, the size or volume of most materials increases with increasing temperature and decreases with decreasing temperature, a phenomenon known as thermal expansion and contraction. Polymers, including PPS, expand when heated and have high thermal expansion coefficients. Thermal expansion issues are generally related to the material's crystal morphology, electronic changes, microstructure, and defects. The principle of thermal expansion and contraction is that molecular motion within a material is affected by temperature fluctuations. As temperature rises, the amplitude of molecular vibration increases, and the material's size increases accordingly. Thermal expansion issues often have significant impacts on practical applications. The thermal expansion coefficient of inorganic particle fillers is much lower than that of polymer resins. Therefore, blending inorganic particles with polymer resins can reduce the thermal expansion coefficient of the composite material. Inorganic particles can fill some of the voids in the resin matrix and increase the constraints on the resin molecular chains, inhibiting their thermal motion. However, the thermal expansion coefficient of traditional inorganic particle fillers is generally positive. Lowering the thermal expansion coefficient of the resin often requires adding large amounts of inorganic fillers to the resin matrix. Excessive additions can significantly degrade the mechanical properties of the resin and increase the difficulty of injection molding. Inorganic ceramic fillers with negative thermal expansion properties can achieve a greater reduction in thermal expansion coefficient with a smaller addition amount, and are currently a more effective and easily controlled method to improve thermal expansion properties.
[0005] Currently, some research has been conducted on low-dielectric PPS composite systems in the prior art. For example, Chinese patent CN112679956A discloses a high-precision, low-overflow, low-warpage, low-dielectric PPS modified material and a preparation method thereof. The modified material comprises, by weight, 19.6-44.2% PPS, 5-11% PPE, 30-45% glass fiber, 4-7% mineral (I), 5-20% mineral (II), 2-5% toughening agent, 0.3-0.45% lubricant, 0.15-0.3% antioxidant, 0.2-0.3% halogen absorber, and 0.15-0.3% desulfurizer. The mineral (I) is selected from an inorganic salt whisker material, and the mineral (II) is selected from hollow microspheres. Chinese patent CN112694753A discloses a low-dielectric PPS / PMP composite material and its preparation method. The composite material comprises the following components by weight: 20-70 parts polyphenylene sulfide; 10-30 parts PMP; 10-30 parts low-dielectric glass fiber; 3-8 parts toughening agent; 0.5-1 part stabilizer; 0.5-1 part lubricant; and 1-5 parts PFA. As can be seen from the aforementioned patent, the current prior art primarily achieves the technical benefits of low-dielectric PPS compositions by adding low-dielectric fillers (such as hollow glass microspheres, low-dielectric glass fibers, and polyhedral cage-type oligomeric silsesquioxanes) or low-dielectric resins (primarily polyolefin resins). Summary of the Invention
[0006] Based on this, the purpose of the present invention is to provide a PPS / PPO composite material with excellent mechanical properties, low dielectric properties and low linear thermal expansion coefficient, which can be applied to the 5G / 6G communication field that requires low dielectric properties and high dimensional stability.
[0007] To achieve the above object, the present invention adopts the following scheme:
[0008] A PPS / PPO composite material is prepared from the following raw materials in parts by weight:
[0009]
[0010] The organic HGS is an organic hollow glass microsphere; the functionalized POSS is a functionalized polyhedral cage-type oligomeric silsesquioxane; and the PPO-g-GMA is polyphenylene ether grafted with glycidyl methacrylate.
[0011] In some embodiments, the PPS / PPO composite material is prepared from the following raw materials in parts by weight:
[0012]
[0013]
[0014] In some embodiments, the PPS / PPO composite material is further preferably prepared from the following raw materials in parts by weight:
[0015]
[0016] In some embodiments, the number average molecular weight of the PPS resin is 28,000 to 36,000; the intrinsic viscosity of the PPO resin is 39.5 to 41.5 mL / g, tested in accordance with GB / T 1632.1-2008 standard, and the solvent is chloroform; the compressive strength of the organized HGS is not less than 55 MPa; the end group of the functionalized POSS contains an epoxy group; the glycidyl methacrylate grafting rate of the PPO-g-GMA is 1.0 to 1.4%; and the particle size of the organized zirconium phosphotungstate is 0.5 to 3.5 μm.
[0017] In some embodiments, the preparation process of the organic HGS is as follows: (1) 100 g of hollow glass microspheres (HGS) are placed in a flask, and then 800-1200 mL of a sodium hydroxide solution with a concentration of 0.3-0.5 mol / L is added, and the mixture is stirred at 50-70° C. for 1-3 h. After stirring, the hollow glass microspheres are washed with deionized water to a pH of 7 and dried for use; (2) 2-4 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane is added to 50-70 mL of anhydrous ethanol to prepare a γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution, and then the pretreated hollow glass microspheres obtained in step (1) are added to the γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution, stirred for 1-2 h, filtered and washed, and dried at 100-120° C. for 2-4 h to finally obtain the organic HGS.
[0018] In some embodiments, the preparation process of the organic zirconium phosphotungstate is as follows: (1) 100g of zirconium phosphotungstate is placed in a flask, and then 800-1200mL of a sodium hydroxide solution with a concentration of 0.3-0.5mol / L is added, and the mixture is stirred at 50-70°C for 1-3h. After stirring, the pH of the zirconium phosphotungstate is washed to 7 with deionized water, and the mixture is dried for use; (2) 3-5g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane is added to 50-70mL of anhydrous ethanol to prepare a γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution, and then the pretreated zirconium phosphotungstate obtained in step (1) is added to the γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution, stirred for 1-2h, filtered and washed, and dried at 100-120°C for 2-4h to finally obtain the organic zirconium phosphotungstate.
[0019] Another object of the present invention is to provide a method for preparing the above-mentioned PPS / PPO composite material.
[0020] The preparation method of the above-mentioned PPS / PPO composite material, specifically the technical scheme, comprises the following steps:
[0021] (1) drying the PPS resin and the PPO resin, and mixing the dried PPS resin, the dried PPO resin, PPO-g-GMA, N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate in proportion;
[0022] (2) mixing the organized HGS and functionalized POSS in proportion;
[0023] (3) The mixed material prepared in step (1) is fed into a parallel twin-screw extruder via a feeder, and the mixed material prepared in step (2) is added to a side (e.g., the fourth zone) of the parallel twin-screw extruder (eight zones in total), and the organic zirconium phosphotungstate is added in proportion to another side (e.g., the third zone) of the parallel twin-screw extruder for melt extrusion and granulation.
[0024] In some embodiments, the drying temperature in step (1) is 80-110° C., and the drying time is 4-8 hours.
[0025] In some embodiments, the drying temperature in step (1) is 90-100° C., and the drying time is 4-6 hours.
[0026] In some embodiments, the process parameters of the parallel twin-screw extruder described in step (3) include: the temperature of zone 1 is 285-305°C, the temperature of zone 2 is 290-310°C, the temperature of zone 3 is 290-310°C, the temperature of zone 4 is 295-315°C, the temperature of zone 5 is 295-315°C, the temperature of zone 6 is 290-310°C, the temperature of zone 7 is 290-310°C, the temperature of zone 8 is 290-310°C, the die head temperature is 290-310°C, and the screw speed is 200-600rpm.
[0027] In some embodiments, the process parameters of the parallel twin-screw extruder described in step (3) include: the temperature of zone 1 is 290-300°C, the temperature of zone 2 is 295-305°C, the temperature of zone 3 is 295-305°C, the temperature of zone 4 is 300-310°C, the temperature of zone 5 is 300-310°C, the temperature of zone 6 is 295-305°C, the temperature of zone 7 is 295-305°C, the temperature of zone 8 is 295-305°C, the die head temperature is 295-305°C, and the screw speed is 300-500rpm.
[0028] In some embodiments, the screw of the parallel twin-screw extruder has a single-thread shape.
[0029] In some embodiments, the ratio L / D of the screw length L to the diameter D of the parallel twin-screw extruder is 35-50.
[0030] In some embodiments, the ratio L / D of the screw length L to the diameter D of the parallel twin-screw extruder is 35-45.
[0031] In some embodiments, the screw of the parallel twin-screw extruder is provided with one or more (including one) meshing block areas and one or more (including one) reverse thread areas.
[0032] In some embodiments, the screw of the parallel twin-screw extruder is provided with two meshing block areas and one reverse thread area.
[0033] In some embodiments, in step (1) and / or step (2), a stirrer is used to perform the mixing step, and the rotation speed of the stirrer is 500-1500 rpm.
[0034] The principle of the PPS / PPO composite material of the present invention is as follows:
[0035] In order to improve the defects of polyphenylene sulfide resin such as high dielectric constant and linear thermal expansion coefficient, the present invention reduces the dielectric constant of the PPS / PPO composite material by compounding PPO resin, organic HGS and functionalized POSS. Among them, PPO resin has no strong polar groups in its molecular structure and its dielectric constant is 2.6 (test frequency is 1GHz); hollow glass microspheres (HGS) are a kind of hollow spherical powdered inorganic non-metallic material, whose main component is soda-lime borosilicate glass, and its cavity contains inert gases such as rarefied nitrogen and carbon dioxide. Therefore, the dielectric constant of hollow glass microspheres is only 1.2 to 1.5 (test frequency is 1GHz). In addition, the compressive strength of hollow glass microspheres is not less than 55MPa to ensure that they will not break during twin-screw extrusion; polyhedral oligomeric silsesquioxane (POSS) has a cage-type nanostructure, which has a large free volume, high porosity and low molecular polarizability. Therefore, the dielectric constant of POSS is 2 to 2.5 (test frequency is 1GHz).
[0036] Typically, the size or volume of most materials increases with increasing temperature and decreases with decreasing temperature, a phenomenon known as thermal expansion and contraction. Polymers, including PPS, expand when heated and have high thermal expansion coefficients. The rigid polyhedrons of zirconium phosphotungstate (ZrPt)—a negative thermal expansion material—are caused by rotational coupling at high temperatures. Specifically, its molecular structure is formed by shared vertices between tetrahedrons and octahedrons. This shared-vertex polyhedral structure causes rotational coupling at these shared vertices when the temperature rises, causing the microscopic distances between the polyhedrons to change, causing the material to appear to contract on a macroscopic scale when heated. Therefore, by blending organic zirconium phosphotungstate with PPS resin, the composite's thermal expansion coefficient can be reduced. The inorganic zirconium phosphotungstate particles can fill some of the voids in the resin matrix and increase the constraints on the resin molecular chains, inhibiting their thermal motion and thus reducing the composite's thermal expansion coefficient. In addition, if the particle size of organic zirconium phosphotungstate is too small, it will not be easily dispersed in the polymer resin matrix. If the particle size is too large, it will easily serve as a stress concentration point in the tensile test or impact test, causing a significant decrease in performance. Therefore, it is more appropriate to select a particle size of 0.5 to 3.5 μm for organic zirconium phosphotungstate.
[0037] PPO-g-GMA has active epoxy groups, and the epoxy groups of organized HGS, functionalized POSS, and organized zirconium phosphotungstate can react with the end groups of PPS and PPO, thereby improving the compatibility and dispersibility of organized HGS, functionalized POSS, and organized zirconium phosphotungstate in the PPS / PPO matrix resin, thereby obtaining a PPS / PPO composite material with low dielectric properties and low linear thermal expansion coefficient.
[0038] The N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide used in the present invention has a melting point of 272°C and a boiling point greater than 360°C. It has good thermal stability during the PPS blending process, and the hindered piperidinyl group can provide antioxidant effects and improve the dyeability of the composition.
[0039] The bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate used in the present invention has a melting point of 239°C and a thermal decomposition temperature of more than 350°C. It has good heat resistance and hydrolysis resistance and can provide excellent color stability and melt stability for PPS during the blending process. At the same time, it can prevent the thermal degradation of PPS during high temperature and inhibit the thermal oxidative discoloration caused by long-term extrusion processing. It also provides nitrogen oxides (NO x ) Color stability in gas environment to prevent gas fumigation discoloration.
[0040] Compared with the prior art, the present invention has the following beneficial effects:
[0041] 1. In order to improve the defects of polyphenylene sulfide resin such as high dielectric constant and linear thermal expansion coefficient, the present invention reduces the dielectric constant of PPS / PPO composite material by compounding PPO resin, organized HGS and functionalized POSS. The epoxy groups of PPO-g-GMA, organized HGS, functionalized POSS and organized zirconium phosphotungstate react with PPS and PPO end groups to improve the compatibility and dispersibility of organized HGS, functionalized POSS and organized zirconium phosphotungstate in PPS / PPO base resin, thereby obtaining a PPS / PPO composite material with low dielectric properties and low linear thermal expansion coefficient.
[0042] 2. The preparation method of the PPS / PPO composite material provided by the present invention has a simple process, is easy to control, has low requirements on equipment, and the equipment used is all general polymer processing equipment, with low investment, which is conducive to industrial production. BRIEF DESCRIPTION OF THE DRAWINGS
[0043] Figure 1 This is a flow chart of the preparation process of a PPS / PPO composite material according to one embodiment of the present invention. DETAILED DESCRIPTION
[0044] In order to further understand the features, technical means, specific objectives and functions achieved by the present invention, and analyze the advantages and spirit of the present invention, the present invention is further described through the following examples.
[0045] The reaction mechanism of the PPS / PPO composite material of the present invention is as follows (see the preparation process flow chart Figure 1 ):
[0046]
[0047] Wherein, R is PPO-g-GMA, or organized HGS, or functionalized POSS, or organized zirconium phosphotungstate.
[0048] It can be seen from the above reaction formula that the epoxy groups of PPO-g-GMA, organized HGS, functionalized POSS, and organized zirconium phosphotungstate react with the end groups of PPS and PPO, thereby improving the compatibility and dispersibility of organized HGS, functionalized POSS, and organized zirconium phosphotungstate in the PPS / PPO matrix resin, thereby obtaining a PPS / PPO composite material with low dielectric properties and low linear thermal expansion coefficient.
[0049] The raw materials used in the Examples of the present invention and the Comparative Examples are as follows:
[0050] PPS resin, with a number average molecular weight of 32,000, was selected from Chongqing Jushi New Material Technology Co., Ltd.
[0051] PPO resin, with an intrinsic viscosity of 40.5 mL / g, was selected from Bluestar Chemical New Materials Co., Ltd.
[0052] HGS, with a compressive strength of 60MPa, was selected from China Steel Group Ma'anshan Mining Institute New Materials Technology Co., Ltd.
[0053] Functionalized POSS, with end groups containing epoxy groups, was selected from Hybrid Plastics Company, USA.
[0054] PPO-g-GMA, with a glycidyl methacrylate grafting rate of 1.2%, was selected from Shenyang Ketong Plastic Co., Ltd.
[0055] Zirconium phosphotungstate, with a particle size of 2 μm, was selected from Ningbo Chemical Raw Materials Co., Ltd.
[0056] Sodium hydroxide was selected from Sinopharm Reagent Chemical Co., Ltd.
[0057] γ-(2,3-Epoxypropoxy)propyltrimethoxysilane was selected from Tianchang Tianchen Chemical Additive Oil Factory.
[0058] Anhydrous ethanol was selected from Sinopharm Reagent Chemical Co., Ltd.
[0059] N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide was selected from Rudong Jinkangtai Chemical Co., Ltd.
[0060] Bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate was selected from Shanghai Dianyao Fine Chemical Co., Ltd.
[0061] The preparation method of the organic HGS used in the following examples and comparative examples comprises the following steps: (1) placing 100 g of hollow glass microspheres (HGS) in a flask, then adding 1000 mL of a 0.4 mol / L sodium hydroxide solution, stirring at 60° C. for 2 h, washing the hollow glass microspheres with deionized water to a pH of 7 after stirring, and drying for later use; (2) adding 3 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 60 mL of anhydrous ethanol to prepare a γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution, then adding the pretreated hollow glass microspheres obtained in step (1) to the solution, stirring for 1.5 h, filtering and washing, and drying at 110° C. for 3 h to obtain the organic HGS.
[0062] The preparation method of the organic zirconium phosphotungstate used in the following examples and comparative examples includes the following steps: (1) placing 100g of zirconium phosphotungstate in a flask, then adding 1000mL of a 0.4mol / L sodium hydroxide solution, stirring at 60°C for 2h, and after stirring, washing the zirconium phosphotungstate to a pH of 7 with deionized water, and drying for use; (2) adding 4g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 60mL of anhydrous ethanol to prepare a γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution, and then adding the pretreated zirconium phosphotungstate obtained in step (1) to the solution, stirring for 1.5h, filtering and washing, and drying at 110°C for 3h to finally obtain the organic zirconium phosphotungstate.
[0063] Example 1:
[0064] This embodiment provides a PPS / PPO composite material, which is prepared from the following raw materials in parts by weight:
[0065]
[0066] The preparation method of the above-mentioned PPS / PPO composite material comprises the following steps:
[0067] (1) drying the PPS resin and the PPO resin at 110° C. for 4 hours, cooling the resin, and adding the cooled PPS resin and the PPO resin, the PPO-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide, and bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphate into a blender for mixing;
[0068] (2) adding the organized HGS and functionalized POSS into another blender and mixing;
[0069] (3) The mixed material prepared in step (1) is fed into a parallel twin-screw extruder through a feeder, and the mixed material prepared in step (2) is added to the side (fourth zone) of the parallel twin-screw extruder (a total of eight zones), and the organic zirconium phosphotungstate is added to the other side (third zone) for melt extrusion and granulation. The process parameters include: the temperature of zone 1 is 305°C, the temperature of zone 2 is 310°C, the temperature of zone 3 is 310°C, the temperature of zone 4 is 315°C, the temperature of zone 5 is 315°C, the temperature of zone 6 is 310°C, the temperature of zone 7 is 310°C, the temperature of zone 8 is 310°C, the die head temperature is 310°C, and the screw speed is 600 rpm.
[0070] The screw shape of the parallel twin-screw extruder is a single-line screw, the ratio L / D of the screw length L to the diameter D is 50, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.
[0071] Example 2:
[0072] This embodiment provides a PPS / PPO composite material, which is prepared from the following raw materials in parts by weight:
[0073]
[0074] The preparation method of the above-mentioned PPS / PPO composite material comprises the following steps:
[0075] (1) drying the PPS resin and the PPO resin at 80° C. for 8 hours, cooling the resin, and adding the cooled PPS resin and the PPO resin, the PPO-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide, and bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphate into a blender for mixing;
[0076] (2) adding the organized HGS and functionalized POSS into another blender and mixing;
[0077] (3) The mixed material prepared in step (1) is fed into a parallel twin-screw extruder via a feeder, and the mixed material prepared in step (2) is added to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and organic zirconium phosphotungstate is added to the other side (third zone) for melt extrusion and granulation. The process parameters include: a temperature of zone 1 of 285° C., a temperature of zone 2 of 290° C., a temperature of zone 3 of 290° C., a temperature of zone 4 of 295° C., a temperature of zone 5 of 295° C., a temperature of zone 6 of 290° C., a temperature of zone 7 of 290° C., a temperature of zone 8 of 290° C., a die head temperature of 290° C., and a screw speed of 200 rpm.
[0078] In this embodiment, the screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 35, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.
[0079] Example 3:
[0080] This embodiment provides a PPS / PPO composite material, which is prepared from the following raw materials in parts by weight:
[0081]
[0082] The preparation method of the above-mentioned PPS / PPO composite material comprises the following steps:
[0083] (1) drying the PPS resin and the PPO resin at 100° C. for 4 hours and then cooling the resin. The cooled PPS resin and the PPO resin, the PPO-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide, and bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphate were added to a blender and mixed.
[0084] (2) adding the organized HGS and functionalized POSS into another blender and mixing;
[0085] (3) The mixed material prepared in step (1) is fed into a parallel twin-screw extruder via a feeder, and the mixed material prepared in step (2) is added to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and organic zirconium phosphotungstate is added to the other side (third zone) for melt extrusion and granulation. The process parameters include: a temperature of 300° C. in zone 1, a temperature of 305° C. in zone 2, a temperature of 305° C. in zone 3, a temperature of 310° C. in zone 4, a temperature of 310° C. in zone 5, a temperature of 305° C. in zone 6, a temperature of 305° C. in zone 7, a temperature of 305° C. in zone 8, a die head temperature of 305° C., and a screw speed of 500 rpm.
[0086] In this embodiment, the screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 45, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.
[0087] Example 4:
[0088] This embodiment provides a PPS / PPO composite material, which is prepared from the following raw materials in parts by weight:
[0089]
[0090] The preparation method of the above-mentioned PPS / PPO composite material comprises the following steps:
[0091] (1) drying the PPS resin and the PPO resin at 90° C. for 6 hours and then cooling the resin. The cooled PPS resin and the PPO resin, the PPO-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate were added to a blender and mixed.
[0092] (2) adding the organized HGS and functionalized POSS into another blender and mixing;
[0093] (3) The mixed material prepared in step (1) is fed into a parallel twin-screw extruder via a feeder, and the mixed material prepared in step (2) is added to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and organic zirconium phosphotungstate is added to the other side (third zone) for melt extrusion and granulation. The process parameters include: a temperature of 290° C. in zone 1, a temperature of 295° C. in zone 2, a temperature of 295° C. in zone 3, a temperature of 300° C. in zone 4, a temperature of 300° C. in zone 5, a temperature of 295° C. in zone 6, a temperature of 295° C. in zone 7, a temperature of 295° C. in zone 8, a die head temperature of 295° C., and a screw speed of 300 rpm.
[0094] In this embodiment, the screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 35, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.
[0095] Example 5:
[0096] This embodiment provides a PPS / PPO composite material, which is prepared from the following raw materials in parts by weight:
[0097]
[0098]
[0099] The preparation method of the above-mentioned PPS / PPO composite material comprises the following steps:
[0100] (1) drying the PPS resin and the PPO resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin and the PPO resin, the PPO-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a blender for mixing;
[0101] (2) adding the organized HGS and functionalized POSS into another blender and mixing;
[0102] (3) The mixed material prepared in step (1) is fed into a parallel twin-screw extruder via a feeder, and the mixed material prepared in step (2) is added to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and organic zirconium phosphotungstate is added to another side (third zone) for melt extrusion and granulation. The process parameters include: a temperature of 295° C. in zone 1, a temperature of 300° C. in zone 2, a temperature of 300° C. in zone 3, a temperature of 300° C. in zone 4, a temperature of 305° C. in zone 5, a temperature of 305° C. in zone 6, a temperature of 300° C. in zone 7, a temperature of 300° C. in zone 8, a die head temperature of 300° C., and a screw speed of 400 rpm.
[0103] In this embodiment, the screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.
[0104] Example 6:
[0105] This embodiment provides a PPS / PPO composite material, which is prepared from the following raw materials in parts by weight:
[0106]
[0107]
[0108] The preparation method of the above-mentioned PPS / PPO composite material comprises the following steps:
[0109] (1) drying the PPS resin and the PPO resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin and the PPO resin, the PPO-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a blender for mixing;
[0110] (2) adding the organized HGS and functionalized POSS into another blender and mixing;
[0111] (3) The mixed material prepared in step (1) is fed into a parallel twin-screw extruder via a feeder, and the mixed material prepared in step (2) is added to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and organic zirconium phosphotungstate is added to another side (third zone) for melt extrusion and granulation. The process parameters include: a temperature of 295° C. in zone 1, a temperature of 300° C. in zone 2, a temperature of 300° C. in zone 3, a temperature of 300° C. in zone 4, a temperature of 305° C. in zone 5, a temperature of 305° C. in zone 6, a temperature of 300° C. in zone 7, a temperature of 300° C. in zone 8, a die head temperature of 300° C., and a screw speed of 400 rpm.
[0112] In this embodiment, the screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.
[0113] Example 7:
[0114] This embodiment provides a PPS / PPO composite material, which is prepared from the following raw materials in parts by weight:
[0115]
[0116] The preparation method of the above-mentioned PPS / PPO composite material comprises the following steps:
[0117] (1) drying the PPS resin and the PPO resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin and the PPO resin, the PPO-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a blender for mixing;
[0118] (2) adding the organized HGS and functionalized POSS into another blender and mixing;
[0119] (3) The mixed material prepared in step (1) is fed into a parallel twin-screw extruder via a feeder, and the mixed material prepared in step (2) is added to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and organic zirconium phosphotungstate is added to another side (third zone) for melt extrusion and granulation. The process parameters include: a temperature of 295° C. in zone 1, a temperature of 300° C. in zone 2, a temperature of 300° C. in zone 3, a temperature of 300° C. in zone 4, a temperature of 305° C. in zone 5, a temperature of 305° C. in zone 6, a temperature of 300° C. in zone 7, a temperature of 300° C. in zone 8, a die head temperature of 300° C., and a screw speed of 400 rpm.
[0120] In this embodiment, the screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.
[0121] Comparative Example 1:
[0122] This comparative example provides a PPS / PPO composite material, which is prepared from the following raw materials in parts by weight:
[0123]
[0124] The preparation method of the above-mentioned PPS / PPO composite material comprises the following steps:
[0125] (1) drying the PPS resin at 95° C. for 5 hours and then cooling the resin. The cooled PPS resin, the PPO-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate were added to a blender and mixed.
[0126] (2) adding the organized HGS and functionalized POSS into another blender and mixing;
[0127] (3) The mixed material prepared in step (1) is fed into a parallel twin-screw extruder via a feeder, and the mixed material prepared in step (2) is added to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and organic zirconium phosphotungstate is added to another side (third zone) for melt extrusion and granulation. The process parameters include: a temperature of 295° C. in zone 1, a temperature of 300° C. in zone 2, a temperature of 300° C. in zone 3, a temperature of 300° C. in zone 4, a temperature of 305° C. in zone 5, a temperature of 305° C. in zone 6, a temperature of 300° C. in zone 7, a temperature of 300° C. in zone 8, a die head temperature of 300° C., and a screw speed of 400 rpm.
[0128] In this comparative example, the screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.
[0129] Comparative Example 2:
[0130] This comparative example provides a PPS / PPO composite material, which is prepared from the following raw materials in parts by weight:
[0131]
[0132] The preparation method of the above-mentioned PPS / PPO composite material comprises the following steps:
[0133] (1) drying the PPS resin and the PPO resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin and the PPO resin, the PPO-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a blender for mixing;
[0134] (2) the mixed material in step (1) is added to a parallel twin-screw extruder via a feeder, and functionalized POSS is added to the side (fourth zone) of the parallel twin-screw extruder (a total of eight zones), and organic zirconium phosphotungstate is added to the other side (third zone) for melt extrusion and granulation. The process parameters include: a zone temperature of 295° C., a zone temperature of 300° C., a zone temperature of 300° C., a zone temperature of 300° C., a zone temperature of 405° C., a zone temperature of 305° C., a zone temperature of 600° C., a zone temperature of 300° C., a zone temperature of 300° C., a zone temperature of 800° C., a die head temperature of 300° C., and a screw speed of 400 rpm.
[0135] In this comparative example, the screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.
[0136] Comparative Example 3:
[0137] This comparative example provides a PPS / PPO composite material, which is prepared from the following raw materials in parts by weight:
[0138]
[0139] The preparation method of the above-mentioned PPS / PPO composite material comprises the following steps:
[0140] (1) drying the PPS resin and the PPO resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin and the PPO resin, the PPO-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a blender for mixing;
[0141] (2) The mixed material prepared in step (1) is fed into a parallel twin-screw extruder via a feeder, and organic HGS is added to the side (fourth zone) of the parallel twin-screw extruder (a total of eight zones), and organic zirconium phosphotungstate is added to the other side (third zone) for melt extrusion and granulation. The process parameters include: zone 1 temperature of 295°C, zone 2 temperature of 300°C, zone 3 temperature of 300°C, zone 4 temperature of 305°C, zone 5 temperature of 305°C, zone 6 temperature of 300°C, zone 7 temperature of 300°C, zone 8 temperature of 300°C, die head temperature of 300°C, and screw speed of 400 rpm.
[0142] In this comparative example, the screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.
[0143] Comparative Example 4:
[0144] This comparative example provides a PPS / PPO composite material, which is prepared from the following raw materials in parts by weight:
[0145]
[0146]
[0147] The preparation method of the above-mentioned PPS / PPO composite material comprises the following steps:
[0148] (1) drying the PPS resin and the PPO resin at 95° C. for 5 hours and then cooling the resin. The cooled PPS resin and the PPO resin, the N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide, and the bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphate were added to a blender and mixed.
[0149] (2) adding the organized HGS and functionalized POSS into another blender and mixing;
[0150] (3) The mixed material prepared in step (1) is fed into a parallel twin-screw extruder via a feeder, and the mixed material prepared in step (2) is added to a side (fourth zone) of the parallel twin-screw extruder (eight zones in total), and organic zirconium phosphotungstate is added to another side (third zone) for melt extrusion and granulation. The process parameters include: a temperature of 295° C. in zone 1, a temperature of 300° C. in zone 2, a temperature of 300° C. in zone 3, a temperature of 300° C. in zone 4, a temperature of 305° C. in zone 5, a temperature of 305° C. in zone 6, a temperature of 300° C. in zone 7, a temperature of 300° C. in zone 8, a die head temperature of 300° C., and a screw speed of 400 rpm.
[0151] In this comparative example, the screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.
[0152] Comparative Example 5:
[0153] This comparative example provides a PPS / PPO composite material, which is prepared from the following raw materials in parts by weight:
[0154]
[0155]
[0156] The preparation method of the above-mentioned PPS / PPO composite material comprises the following steps:
[0157] (1) drying the PPS resin and the PPO resin at 95° C. for 5 hours, cooling the resin, and adding the cooled PPS resin and the PPO resin, the PPO-g-GMA, N,N′-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide, and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate into a blender for mixing;
[0158] (2) adding the organized HGS and functionalized POSS into another blender and mixing;
[0159] (3) The mixed material prepared in step (1) is fed into a parallel twin-screw extruder via a feeder, and the mixed material prepared in step (2) is added to the side (fourth zone) of the parallel twin-screw extruder (a total of eight zones) for melt extrusion and granulation. The process parameters include: a temperature of zone 1 of 295° C., a temperature of zone 2 of 300° C., a temperature of zone 3 of 300° C., a temperature of zone 4 of 305° C., a temperature of zone 5 of 305° C., a temperature of zone 6 of 300° C., a temperature of zone 7 of 300° C., a temperature of zone 8 of 300° C., a die head temperature of 300° C., and a screw speed of 400 rpm.
[0160] In this comparative example, the screw shape of the parallel twin-screw extruder is a single-line thread, the ratio L / D of the screw length L to the diameter D is 40, the screw is provided with two meshing block areas and one reverse thread area, and the mixer in step (1) and step (2) is a high-speed mixer with a rotation speed of 1000 rpm.
[0161] The following is a list of raw material compositions for Examples and Comparative Examples (Table 1).
[0162] Table 1 Summary of raw material compositions by weight for Examples and Comparative Examples
[0163]
[0164]
[0165] The addition amount of N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarboxamide and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate in the above examples and comparative examples is 0.3 parts.
[0166] Examples 1 to 7 are for preparing PPS / PPO composite materials by adjusting the addition amounts of PPS resin, PPO resin, organized HGS, functionalized POSS, PPO-g-GMA, and organized zirconium phosphotungstate. Comparative Example 1 is for preparing PPS / PPO composite materials without adding PPO resin, Comparative Example 2 is for preparing PPS / PPO composite materials without adding organized HGS, Comparative Example 3 is for preparing PPS / PPO composite materials without adding functionalized POSS, Comparative Example 4 will not add PPO-g-GMA to prepare PPS / PPO composite materials, and Comparative Example 5 will not add organized zirconium phosphotungstate to prepare PPS / PPO composite materials.
[0167] The PPS / PPO composite materials prepared in the above examples and comparative examples were subjected to the following performance tests:
[0168] Tensile properties: tested according to GB / T 1040-2006 standard, with a tensile rate of 50 mm / min.
[0169] Impact performance: tested according to GB / T 1843-2008 standard, specimen thickness is 4mm.
[0170] Dielectric constant: tested according to GB / T 5597-1999 standard, the test frequency is 1 GHz; for this composite material, the lower the dielectric constant, the better.
[0171] Linear thermal expansion coefficient: The linear thermal expansion coefficient of the composite material was tested using a static thermal mechanical analyzer TMA Q400 (TA Instruments, USA). Specifically, the linear thermal expansion coefficient of the composite material columnar sample was measured as a function of temperature. The test temperature range was 40–300°C, and the heating rate was 5°C / min.
[0172] The performance test results are shown in Table 2.
[0173] Table 2 Performance summary of PPS / PPO composite materials of Examples and Comparative Examples
[0174]
[0175]
[0176] From Table 2 we can see that:
[0177] As the amount of PPS resin added decreases and the amount of PPO resin added increases, the tensile strength and notched impact strength of the PPS / PPO composite material gradually decrease. This is because the tensile strength and notched impact strength of the PPS resin matrix are higher than those of the PPO resin. When the amount of PPS resin added decreases, the tensile strength and notched impact strength of the PPS / PPO composite material also decrease.
[0178] With the increase of the addition amount of PPO resin, organized HGS and functionalized POSS, the dielectric constant of PPS / PPO composites gradually decreases. This is because PPO resin has no strong polar groups in its molecular structure and its dielectric constant is 2.6 (test frequency is 1 GHz); hollow glass microspheres (HGS) are a kind of hollow spherical powdered inorganic non-metallic material, whose main component is soda lime borosilicate glass, and its cavity contains inert gases such as rarefied nitrogen and carbon dioxide. Therefore, the dielectric constant of hollow glass microspheres is only 1.2 to 1.5 (test frequency is 1 GHz). In addition, the compressive strength of hollow glass microspheres is not less than 55 MPa to ensure that they are not broken during twin-screw extrusion; polyhedral oligomeric silsesquioxane (POSS) has a cage-type nanostructure with a large free volume, high porosity and low molecular polarizability. Therefore, the dielectric constant of POSS is 2 to 2.5 (test frequency is 1 GHz); therefore, the composite use of PPO resin, organic HGS and functionalized POSS can reduce the dielectric constant of PPS / PPO composite materials.
[0179] As the addition of organic zirconium phosphotungstate increases, the linear thermal expansion coefficient of the PPS / PPO composite material gradually decreases. This is because the organic zirconium phosphotungstate can reduce the thermal expansion coefficient of the composite material after being blended with PPS resin. The inorganic zirconium phosphotungstate particles can fill some of the voids in the resin matrix and increase the constraints on the resin molecular chains, inhibiting the thermal motion of the molecular chains, thereby reducing the thermal expansion coefficient of the composite material.
[0180] In summary, by adjusting the addition amounts of PPS resin, PPO resin, organized HGS, functionalized POSS, PPO-g-GMA, and organized zirconium phosphotungstate, with the synergistic cooperation of various additives, the PPS / PPO composite material of the present invention with excellent mechanical properties, low dielectric properties, and low linear thermal expansion coefficient can be obtained.
[0181] Compared with Example 7, Comparative Example 1 is a PPS / PPO composite material prepared without adding PPO resin. Since PPO resin has no strong polar groups in its molecular structure, its dielectric constant is 2.6 (test frequency is 1 GHz). Therefore, the dielectric constant of Comparative Example 1 is higher than the dielectric constant of Example 7.
[0182] Compared with Example 7, Comparative Example 2 is a PPS / PPO composite material prepared without adding organic HGS. Since hollow glass microspheres (HGS) are a hollow spherical powdered inorganic non-metallic material whose main component is soda-lime borosilicate glass, and its cavity is filled with inert gases such as dilute nitrogen and carbon dioxide, the dielectric constant of the hollow glass microspheres is only 1.2 to 1.5 (test frequency is 1 GHz). Therefore, the dielectric constant of Comparative Example 2 is higher than that of Example 7.
[0183] Compared with Example 7, Comparative Example 3 is a PPS / PPO composite material prepared without adding functionalized POSS. Since polyhedral oligomeric silsesquioxane (POSS) has a cage-type nanostructure, it has a large free volume, high porosity and low molecular polarizability. Therefore, the dielectric constant of POSS is 2 to 2.5 (test frequency is 1 GHz). Therefore, the dielectric constant of Comparative Example 3 is higher than that of Example 7.
[0184] Compared with Example 7, Comparative Example 4 does not add PPO-g-GMA to prepare a PPS / PPO composite material. Since PPO-g-GMA has an active epoxy group, and the epoxy groups of the organized HGS, functionalized POSS, and organized zirconium phosphotungstate can react with PPS and PPO end groups, thereby improving the compatibility and dispersibility of the organized HGS, functionalized POSS, and organized zirconium phosphotungstate in the PPS / PPO base resin, thereby obtaining a PPS / PPO composite material with low dielectric properties and low linear thermal expansion coefficient. Therefore, the tensile strength and notched impact strength of Comparative Example 4 are lower than the tensile strength and notched impact strength of Example 7, respectively, and the dielectric constant of Comparative Example 4 is higher than the dielectric constant of Example 7.
[0185] Compared with Example 7, Comparative Example 5 does not add organic zirconium phosphotungstate to prepare the PPS / PPO composite material. Since the organic zirconium phosphotungstate can reduce the thermal expansion coefficient of the composite material after being blended with the PPS resin, its inorganic zirconium phosphotungstate particles can fill part of the gaps in the resin matrix, increase the constraints on the resin molecular chains, and inhibit the thermal motion of the molecular chains, thereby reducing the thermal expansion coefficient of the composite material. Therefore, the linear thermal expansion coefficient of Comparative Example 5 is higher than that of Example 7.
[0186] The technical features of the above-mentioned embodiments can be combined arbitrarily. In order to make the description concise, not all possible combinations of the technical features in the above-mentioned embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0187] The above-described embodiments merely illustrate several implementations of the present invention, and while their descriptions are relatively specific and detailed, they should not be construed as limiting the scope of the patent. It should be noted that a person skilled in the art would be able to make numerous variations and improvements without departing from the spirit of the present invention, all of which fall within the scope of protection of the present invention. Therefore, the scope of protection of the patent for this invention shall be determined by the appended claims.
Claims
1. A PPS / PPO composite material, characterized in that: It is prepared from the following raw materials in parts by weight: 60-80 parts of PPS resin, 20-40 parts of PPO resin, The total weight of PPS resin and PPO resin is 100 parts. The organic HGS is an organic hollow glass microsphere; the functionalized POSS is a functionalized polyhedral cage-type oligomeric silsesquioxane; and the PPO-g-GMA is polyphenylene ether grafted with glycidyl methacrylate.
2. The PPS / PPO composite material according to claim 1, characterized in that: It is prepared from the following raw materials in parts by weight: 63-77 parts of PPS resin, 23-37 parts of PPO resin, The total weight of PPS resin and PPO resin is 100 parts.
3. The PPS / PPO composite material according to claim 2, characterized in that: It is prepared from the following raw materials in parts by weight: 67-73 parts of PPS resin, PPO resin 27-33 parts, The total weight of PPS resin and PPO resin is 100 parts. 0.25 to 0.35 parts of N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide, 0.25 to 0.35 parts of bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate 4. The PPS / PPO composite material according to any one of claims 1 to 3, characterized in that: The number average molecular weight of the PPS resin is 28,000 to 36,000; and / or the intrinsic viscosity of the PPO resin is 39.5 to 41.5 mL / g; and / or the compressive strength of the organic HGS is not less than 55 MPa; and / or the end groups of the functionalized POSS contain epoxy groups; and / or the glycidyl methacrylate grafting rate of the PPO-g-GMA is 1.0 to 1.4%; and / or the particle size of the organic zirconium phosphotungstate is 0.5 to 3.5 μm.
5. The PPS / PPO composite material according to any one of claims 1 to 3, characterized in that: The preparation process of the organic HGS is as follows: (1) placing 100 g of hollow glass microspheres in a flask, then adding 800-1200 mL of a sodium hydroxide solution with a concentration of 0.3-0.5 mol / L, stirring at 50-70° C. for 1-3 h, washing the hollow glass microspheres with a pH of 7 with deionized water after stirring, and drying for use; (2) adding 2-4 g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane to 50-70 mL of anhydrous ethanol to prepare a γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution, then adding the pretreated hollow glass microspheres obtained in step (1) to the γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution, stirring for 1-2 h, filtering and washing, and drying at 100-120° C. for 2-4 h, and finally obtaining the organic HGS; And / or, the preparation process of the organic zirconium phosphotungstate is as follows: (1) 100g of zirconium phosphotungstate is placed in a flask, and then 800-1200mL of a sodium hydroxide solution with a concentration of 0.3-0.5mol / L is added, and the mixture is stirred at 50-70°C for 1-3h. After stirring, the pH value of the zirconium phosphotungstate is washed to 7 with deionized water, and then dried for use; (2) 3-5g of γ-(2,3-epoxypropoxy)propyltrimethoxysilane is added to 50-70mL of anhydrous ethanol to prepare a γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution, and then the pretreated zirconium phosphotungstate obtained in step (1) is added to the γ-(2,3-epoxypropoxy)propyltrimethoxysilane solution, stirred for 1-2h, filtered and washed, and dried at 100-120°C for 2-4h to finally obtain the organic zirconium phosphotungstate.
6. A method for preparing the PPS / PPO composite material according to any one of claims 1 to 5, characterized in that: The following steps are involved: (1) drying a PPS resin and a PPO resin, and mixing the dried PPS resin, the dried PPO resin, PPO-g-GMA, N,N'-bis(2,2,6,6-tetramethyl-4-piperidinyl)-1,3-benzenedicarbamide and bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphate in proportion; (2) mixing the organized HGS and the functionalized POSS in proportion; (3) adding the mixed material prepared in step (1) into a parallel twin-screw extruder via a feeder, and adding the mixed material prepared in step (2) to the side of the parallel twin-screw extruder, and adding the organic zirconium phosphotungstate in proportion to the other side of the parallel twin-screw extruder for melt extrusion and granulation; Wherein, the drying temperature in step (1) is 80-110° C., and the drying time is 4-8 hours; and / or, the process parameters of the parallel twin-screw extruder in step (3) include: zone one temperature of 285-305° C., zone two temperature of 290-310° C., zone three temperature of 290-310° C., zone four temperature of 295-315° C., zone five temperature of 295-315° C., zone six temperature of 290-310° C., zone seven temperature of 290-310° C., zone eight temperature of 290-310° C., die head temperature of 290-310° C., and screw speed of 200-600 rpm.
7. The preparation method according to claim 6, characterized in that: The drying temperature in step (1) is 90-100° C., and the drying time is 4-6 hours; and / or the process parameters of the parallel twin-screw extruder in step (3) include: zone one temperature of 290-300° C., zone two temperature of 295-305° C., zone three temperature of 295-305° C., zone four temperature of 300-310° C., zone five temperature of 300-310° C., zone six temperature of 295-305° C., zone seven temperature of 295-305° C., zone eight temperature of 295-305° C., die head temperature of 295-305° C., and screw speed of 300-500 rpm.
8. The preparation method according to any one of claims 6 to 7, characterized in that: The screw shape of the parallel twin-screw extruder is a single-thread; and / or the ratio L / D of the screw length L and diameter D of the parallel twin-screw extruder is 35 to 50; and / or the screw of the parallel twin-screw extruder is provided with more than one meshing block area and more than one reverse thread area.
9. The preparation method according to claim 8, characterized in that: The ratio L / D of the screw length L to the diameter D of the parallel twin-screw extruder is 35-45; and / or, the screw of the parallel twin-screw extruder is provided with two meshing block areas and one reverse thread area.
10. The preparation method according to any one of claims 6 to 7, characterized in that: In step (1) and / or step (2), a stirrer is used to perform the mixing step, and the rotation speed of the stirrer is 500 to 1500 rpm.
Citation Information
Patent Citations
High-precision low-overflow low-warpage low-dielectric PPS modified material and preparation method thereof
CN112679956A
Low-dielectric PPS / PMP composite material and preparation method thereof
CN112694753A
Negative thermal expansion material and composite material including the same
CN108025915A
Low-dielectric-constant polyphenylene sulfide composition and preparation method thereof
CN111334042A
PPO / PPS composition and preparation method thereof
CN116875028A